Accumulation of Metals in a Natural Wetland that Receives Acid Mine Drainage - Thomas Wildeman; Monica Pavlik (Society for Mining, Metallurgy & Exploration, 2000)
Water from the Forest Queen mine adit near Silverton, Colorado drains into a natural wetland. Because the pH of the water averages 5 and the iron concentration averages 18 mg/L, it was thought that the wetland might naturally treat the water. Of most concern with respect to the aquatic environment is zinc whose concentration averages 0.60 mg/L. Starting in October 1997, the surface waters, ground waters in the peat substrate, and the sediments in the wetland were sampled and analyzed four times over the course of four months. The adit water primarily remains as surface water where Fe, minor amounts of Al, and no Zn are removed. After the adit water enters the peat, then it is found that the pH rises to 5.8-6.5 and sulfate is reduced. The removal of Zn and A1 is caused by these two changes. However, Fe in its reduced state is quite soluble and may be remobilized in the reduced environment of the peat.